PERANAN ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN SEKTOR PERDAGANGAN - NOVIANDRI, TIO (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Financial decrease condition in company which they have bankcruptcy condition, often called financial distress. The aims of this research is to investegate the effect of current ratio, debt to equity ratio, operating profit margin, and total asset turnover on financial distress. The sample in this research is Trade Sector Companies which are listed in Indonesia Stock Exchange in the period of 2008-2012. Totally, there are 17 listed companies which are selected using purposive sampling method. To analyze data, this research employs regression logistics. The results of this research indicate that current ratio, debt to equity ratio, operating profit margin, and total asset turnover has significant effect on financial distress. Keywords: financial distress, financial ratios, trade sector. .